Metabolic and functional changes in retinitis pigmentosa: comparing retinal vessel oximetry to full‐field electroretinography, electrooculogram and multifocal electroretinography. (22nd October 2015) - Todorova, Margarita G.; Türksever, Cengiz; Schötzau, Andreas; Schorderet, Daniel F.; Valmaggia, Christophe
Abstract: Purpose: To determine a relationship between the retinal vessel saturation alterations and the residual retinal function measured by means of full‐field electroretinography (full‐field ERG), electrooculogram (EOG) and multifocal electroretinography (mfERG) in patients with retinitis pigmentosa (RP). Methods: Retinal vessel oximetry (RO), full‐field ERG, EOG and mfERG were performed on 43 eyes of 22 patients suffering from RP and were compared to those of 26 eyes of 13 healthy controls. The oxygen saturation in the first and second branch retinal arterioles (A‐SO2 ) and venules (V‐SO2 ) was measured, and their difference (A‐V SO2 ) was calculated. Full‐field ERG amplitudes, EOG parameters and averaged mfERG response amplitudes (within central 3°, between 3° and 8°, 8° and 15°, 15° and 24°) were evaluated in relation to the RO measurements. Results: V‐SO2 correlated negatively with the full‐field ERG and EOG values, with increasing functional damage the V‐SO2 was higher. The RP group was well distinguished from the controls when the RO measurements were correlated to the averaged N1 (baseline to trough), but also to the N1P1 (trough‐to‐peak) mfERG response amplitudes. Receiver operating characteristic (ROC) curve of V‐SO2, compared to those of N1 and N1P1 mfERG response averages (15–24°), presented a high differential margin between RP and controls (p < 0.001), shown by an area under the ROC curve of 0.912 (95% CI: 0.840–0.984). Conclusion: Retinal vessel saturation showed a significant relation to full‐field ERG, EOG and mfERG. Thus, retinal vessel oximetry could potentially complement electrophysiological tests in monitoring disease progression in patients with RP.